Characterisation of the lipolytic enzymatic activities of fungal rizoenzymes from Rhizopus oryzae in comparison to pancreatin from pigs - Schön C.; Wacker R.; Rothe M.; Lipowicz B.; Iphöfer A. (Sciendo, 2024)
In case of exocrine pancreatic insufficiency (EPI), the replacement of digestive enzymes with, for example porcine pancreatin or fungal rizoenzymes, is unavoidable under certain conditions. Current guidelines indicate that preparations from porcine pancreas have more advantageous physicochemical properties compared to those from fungi, especially at high bile salt concentrations, and that the latter can, therefore, only be used clinically to a limited extent. Since rizoenzymes are increasingly used in clinical practice, the present in vitro study investigated efficiency of enzymatic activity of rizoenzymes in comparison to pancreatin under various physiological and partly extreme environmental conditions.